2013
DOI: 10.22490/21456453.978
|View full text |Cite
|
Sign up to set email alerts
|

Aporte de Nitrógeno al suelo por Mucuna pruriens y su efecto sobre el rendimiento de maíz dulce (Zea mays L.)

Abstract: <p>Se evaluó el aporte de nitrógeno a un suelo <em>Typic Haplustalfs </em>por parte de la especie <em>Mucuna pruriens </em>como abono verde y cobertura, y su efecto sobre el rendimiento de maíz dulce (<em>Zea mays L.</em>). Se encontró incremento máximo en el suelo de 201 kg ha-1, la cuál contrastó con el testigo. El tratamiento donde se usó el abono verde más compost 2.5 t ha-1 y fertilizante de síntesis 125 kg ha-1, obtuvo el mayor rendimiento de grano seco de maíz 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
(5 reference statements)
0
3
0
1
Order By: Relevance
“…Other studies have also reported that C. ensiformis produced up to 8.55 t ha -1 of dry biomass and fixed up to 112.4 kg ha -1 of N in marginal environments (PAIvA et al, 2014). Furthermore, studies have shown that M. pruriens had a maximum of 201 kg ha -1 of N in the soil (REYES et al, 2013). When legumes intercropped with maize, this intercropping system offers greater benefits for the cereal by fixing N. Enhanced N uptake was reported by different researchers under a varied intercropping system where legume was considered as a component, for example, maize + sunn hemp intercropping (CHIEZA et al, 2017) and maize-soybean intercropping system (OWUSU & SADICK, 2016).…”
Section: Nitrogen Fixationmentioning
confidence: 99%
“…Other studies have also reported that C. ensiformis produced up to 8.55 t ha -1 of dry biomass and fixed up to 112.4 kg ha -1 of N in marginal environments (PAIvA et al, 2014). Furthermore, studies have shown that M. pruriens had a maximum of 201 kg ha -1 of N in the soil (REYES et al, 2013). When legumes intercropped with maize, this intercropping system offers greater benefits for the cereal by fixing N. Enhanced N uptake was reported by different researchers under a varied intercropping system where legume was considered as a component, for example, maize + sunn hemp intercropping (CHIEZA et al, 2017) and maize-soybean intercropping system (OWUSU & SADICK, 2016).…”
Section: Nitrogen Fixationmentioning
confidence: 99%
“…A distance of 0.20 m was considered between plants and 0.80 m between rows to obtain a density of 62 500 plants ha -1 , for Vigna unguiculata and Phaseolus lunatus (Jara-Claudio and Alejos-Patiño 2016; Batista de Sousa et al, 2020). Mucuna was planted with a distance of 0.50 m between plants and 0.80 m between rows to achieve a density of 25 000 plants ha -1 (Sanclemente- Reyes et al, 2013;Rojas-Molina et al, 2019). During the development of the GM, the agronomic management consisted of pest and disease control, and weed management.…”
Section: Planting and Incorporation Of Green Manurementioning
confidence: 99%
“…En cuanto a la relación C:/N en el suelo, los valores obtenidos para todos los tratamientos estuvieron llegando al límite inferior, siendo los tratamientos M.pruriens, M.pruriens+fertilización y Testigo los más altos, en estos tres tratamientos citados el denominador común fue la presencia de M.pruriens, al menos en dos de ellos, lo cual puede interpretarse según Flores (2010) y Sanclemente et al (2013), que cuando la relación C/N es baja significa que hay mucho nitrógeno y poco carbono. El Nitrógeno es liberado por los abonos verdes como la M.pruriens en éste caso y como es usual en otras investigaciones (Cobo et al, 2002, Handayanto, Cadish y Giller 1994, una parte de ese nitrógeno es tomado por los microorganismos, otra parte se incorpora al suelo y otra se absorbe por las plantas.…”
Section: Artículos Científicosunclassified